MICROORGANISMS - A SOURCE OF BIOLOGICAL CONTAMINATION OF FUELS AND LUBRICANTS IN STORAGE TANKS - Puzik, Sergiy; Trofimov, Igor (Problems of Friction and Wear, 2023)
It has been found that the presence of biological contaminants in tanks, such as corrosion products, microorganisms of various origins, resinous deposits of fuels and lubricants (F&L), can lead to their destruction and a decrease in the condition of F&L, which negatively affects the safety of aircraft flights and the operation of special vehicles. Yeast-like fungi and bacteria were isolated and identified from samples of aircraft TS-1 and diesel fuel: the substrate-specific gassing fungus Hormoconis resinae (Cladosporium resinae) and bacterial cultures of both Gram-positive (G+), Gram-negative (G-) and G-variable "associations". It was found that these microorganisms are able to grow in the presence of F&L, forming powerful colonies of motile and non-motile rod-shaped bacteria. Based on the analysis of the data obtained, it is assumed that in the detected biological contamination of F&L, microorganisms can coexist only in the composition of biofilms. This assumption needs to be further investigated, as does the claim that the adhesion ability of F&L is an important step in the process of their utilization by microorganisms.